Designing an Effective Learning Environment for Language Learning During the Covid-19 Pandemic - Betoncu, Olkan; Faslı, Funda G.; Ozdamli, Fezile (Frontiers in Psychology, 2021)
Effects of the rapid developments in the IT of the 21st century and the COVID-19 pandemic have been experienced in education as well; the necessity to use technology for educational purposes originated. Mobile phones, which hold a more important place than computers, also became a part of education. In today’s world, it is possible to access educational content without any limitation of time and space. Individuals who desire to learn a new language but cannot do so due to financial difficulties or free time have moved towards mobile learning methods. “YIT101” mobile application designed to teach Turkish as a foreign language independent from time and location and targets basic Turkish A1 level course content. This application enables accessing information when needed and learning Turkish as a foreign language outside the classroom environment by saving time and as independent from a formal instructor.